2021
DOI: 10.2196/25767
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Lived Experience of North American Dental Patients With a Single-Tooth Implant in the Upper Front Region of the Mouth: Protocol for a Qualitative Study

Abstract: Background Assessment of the subjective experiences of individuals with maxillary anterior (ie, the upper front region of the mouth) single-tooth implants is limited mainly to quantitative measurements of satisfaction with appearance. Interestingly, there is unexplained variability in the relationship between satisfaction and appearance. Objective This qualitative study protocol aims to explore and better understand the satisfaction with appearance and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…It is expected that the analysis from the current project will provide recommendations to improve the students' academic curriculum pre-clinical experience in the form of three publications in peer-reviewed Scopus-indexed journals 7,8 . This will be one publication for each subject intended to be evaluated (i.e., head and neck anatomy, dental anatomy, and removable prosthodontics).…”
Section: Dissemination Of the Resultsmentioning
confidence: 99%
“…It is expected that the analysis from the current project will provide recommendations to improve the students' academic curriculum pre-clinical experience in the form of three publications in peer-reviewed Scopus-indexed journals 7,8 . This will be one publication for each subject intended to be evaluated (i.e., head and neck anatomy, dental anatomy, and removable prosthodontics).…”
Section: Dissemination Of the Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that interactive teaching mode was as excellent as conventional teaching methods, and in certain trials, it was proven to be the most effective learning approach [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Compared to traditional teaching approaches, interactive teaching has a considerable impact on cognitive achievement and learning attitude.…”
Section: Discussionmentioning
confidence: 99%
“…subscribed to van Manen's recommendation for a dynamic interaction between six research steps that allowed flexibility in working intermittently or simultaneously, back and forth between steps, as a form of an "interpretative circle," depending on the evolving research needs [4,5]. The framework proposed by van Manen included the following steps: "turning to the nature of lived experience," "investigating experience as we live it," "reflecting on the essential themes that characterize the phenomenon," "describing the phenomenon in the art of writing and rewriting," "maintaining a strong and oriented relation to the phenomenon," and "balancing the research context by considering the parts and the whole" [6]. The results of this qualitative study were interpreted and presented by arranging them as themes and subthemes, relating these to the "whole", relative to understanding the phenomenon in question.…”
Section: Discussionmentioning
confidence: 99%
“…The dataset in this research article contains the data from nine (55.6% men) adult patients who had a missing tooth replaced with a single crown supported by an osseointegrated titanium implant performed by postgraduate students from the Periodontology and Prosthodontology departments at a Canadian educational institution. The number of included participants was aligned with the estimation stipulated in the study protocol [6], which was based on achieving the research data saturation of previous qualitative studies, including between six and twelve individual interviews [1,[7][8][9][10].…”
Section: Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation